The Role of The Koran Therapy on Anxiety and Immunity of Hospitalized Patients - Hammad Hammad (Jurnal Ners, 2009)
Introduction: Patient in the hospital faced with anxiety, in feel stronge with the hospital, medicine and treatment action although unsure prognosis of desease. The anxiety will inflict a financial loss because it will influence the attitude of the patient and immunology respons that will effect on how long the patient stay in the hospital and how much cost of treatment. This study was aimed to explain the anxiety level and imunity of patient in the hospital before and after The Al Qur’an therapy. Method: This study used Pre experiment pre-posttest design  involved 7 respondents, taken by accidental sampling.  The independent variable was The Al Qur’an therapy and the dependent variable were anxiety level and imunity (basofil, eosinofil, monocyt, limfocyt  and leucocyt). Anxiety level were collected by Hamilton Anxiey Rating Scale and the imunity were gotten from laboratory result of basofil, eosinofil, monocyt, limfocyt  and leucocyt . Data were analyzed using Wilcoxon Sign Rank Test for anxiety level and Mc Nemar for imunity with level of significance α ≤ 0.05.Result:  Results showed that The Al Qur’an therapy has an effect on decreasing anxiety level (p=0.016). In contrast, there was no effect on imunity after therapy (p = 0,625).  incision. It can be concluded that the Koran therapy was proven to reduce anxiety level and increased on imunity on patients hospitalized. Discussion: For future Further studies should be developed and include larger responden to obtain more accurate results.